2016
DOI: 10.4236/ojg.2016.67045
|View full text |Cite
|
Sign up to set email alerts
|

Application of Self-Organizing Map for Exploration of REEs’ Deposition

Abstract: Varieties of approaches and algorithms have been presented to identify the distribution of elements. Previous researches based on the type of problem, categorized their data in proper clusters or classes. This means that the process of solution could be supervised or unsupervised. In cases, where there is no idea about dependency of samples to specific groups, clustering methods (unsupervised) are applied. About geochemistry data, since various elements are involved, in addition to the complex nature of geoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These methods have been applied in diverse aspects of science and engineering, somewhat in geochemistry and never for exploration of REEs. The papers of Sarparandeh and Hezarkhani (2016) and Zaremotlagh and Hezarkhani (2016) are the only efforts which have been made in this area. However, there is no study that applies and compares several types of algorithms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have been applied in diverse aspects of science and engineering, somewhat in geochemistry and never for exploration of REEs. The papers of Sarparandeh and Hezarkhani (2016) and Zaremotlagh and Hezarkhani (2016) are the only efforts which have been made in this area. However, there is no study that applies and compares several types of algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Abedi et al the used the SOM and fuzzy k-means techniques to provide a deposit exploration map for the Now Chun copper deposit in Iran. Sarparandeh and Hezarkhani (2016) examined the application of SOMs in evaluation of the geochemical distribution of REEs in the Choghart Fe-REE deposit in Bafq district and showed its good performance. Generally, in cases where there are too many parameters and samples, pattern recognition is a suitable approach for data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on Kiruna-type iron oxide-apatite (IOA) deposits in Bafq mining district showed the potential for REEs (i.e. SeChahun [5,35]; Choghart: [34,37]. In addition, some numerical models were applied to predict the hidden patterns of REEs in Choghart iron ore deposit [34,46].…”
Section: Introductionmentioning
confidence: 99%
“…SeChahun [5,35]; Choghart: [34,37]. In addition, some numerical models were applied to predict the hidden patterns of REEs in Choghart iron ore deposit [34,46]. The REEs are mainly concentrated in specific types of rocks and deposits.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The unassigned data are allocated to their appropriate clusters (appendix) (Kainulainen and Kainulainen, 2002). Sarparandeh and Hezarkhani (2016) implemented this method for delineating lithology and exploring rare elements. Jin (1994) also implemented BSAS for two-dimensional subsidence analysis.…”
Section: Modified Basic Sequential Algorithmic Schemementioning
confidence: 99%